Pre and post-competitive anxiety and self-confidence and their relationship with technical-tactical performance in high-level men's padel players - Conde-Ripoll, Rafael; Escudero-Tena, Adrián; Bustamante-Sánchez, Álvaro (Frontiers in Sports and Active Living, 2024)
Introduction This study aimed to analyze the variations in pre- and post-competitive anxiety and self-confidence considering match outcomes, the performance according to the result and the correlation among performance and psychological variables. Methods The sample consisted on 12 matches in which 11 high-level padel players from Finland (top 24) voluntarily participated. CSAI-2R and STAI-S were used to assess psychological variables and technical-tactical performance was evaluated by a certified padel coach. Results Losing players presented higher cognitive (p = .004), somatic (p = .020) and state (p = .001) anxiety and lower selfconfidence (p = .014), and winning players showed higher state anxiety (p = .022), after than before the matches. Post-match, winning players exhibited higher self-confidence (p = .015) than losing players. Winning players made more winners (p = .010) than losing players. There are direct correlations between unforced errors and post-state anxiety (p = .015), unforced errors and state anxiety (p = .009) and winners and cognitive anxiety (p = .033), in winning players; between generators of forced error and post-cognitive anxiety (p = .034), forced errors and cognitive anxiety in losing players (p = .001). There are indirect correlations between forced errors and pre-cognitive anxiety (p = .009), winners and somatic anxiety (p = .046), unforced errors and state anxiety (p = .042) in losing players. Discussion The outcomes imply the need for intervention programs to equip players, especially those facing defeat, with tools for anxiety management and self-confidence enhancement. Likewise, coaches are advised to incorporate exercises that promote the occurrence of winners.